Household-level dynamics of food waste production and related beliefs, attitudes, and behaviours in Guelph, Ontario. (January 2015) - Parizeau, Kate; von Massow, Mike; Martin, Ralph
Highlights: We combined household waste stream weights with survey data. We examine relationships between waste and food-related practices and beliefs. Families and large households produced more total waste, but less waste per capita. Food awareness and waste awareness were related to reduced food waste. Convenience lifestyles were differentially associated with food waste. Abstract: It has been estimated that Canadians waste 27 billion of food annually, and that half of that waste occurs at the household level (Gooch et al., 2010 ). There are social, environmental, and economic implications for this scale of food waste, and source separation of organic waste is an increasingly common municipal intervention. There is relatively little research that assesses the dynamics of household food waste (particularly in Canada). The purpose of this study is to combine observations of organic, recyclable, and garbage waste production rates to survey results of food waste-related beliefs, attitudes, and behaviours at the household level in the mid-sized municipality of Guelph, Ontario. Waste weights and surveys were obtained from 68 households in the summer of 2013. The results of this study indicate multiple relationships between food waste production and household shopping practices, food preparation behaviours, household waste management practices, and food-related attitudes, beliefs, and lifestyles. Notably, we observed that food awareness, waste awareness, family lifestyles, and convenience lifestyles were related to food waste production. We conclude that it is important to understand the diversity of factors that can influence food wasting behaviours at the household level in order to design waste management systems and policies to reduce food waste.